Effectiveness of Acupressure Therapy in Cancer Patients with Constipation - Munqiidz Zahrawaani; Allenidekania Allenidekania; Zesi Aprillia (Knowledge Dynamics, 2024)
Background: Constipation in cancer patients on chemotherapy is common (31.7%), worsened by medication side effects. Laxatives worsen symptoms, prompting exploration of alternative therapies like acupressure, particularly in pediatric cases. Indonesian National Hospital research assesses acupressure's effectiveness in managing chemotherapy-induced constipation. This study aims to identifying the effectiveness of acupressure therapy in pediatric cancer patients with constipation. Methods: experimental research methods on cancer children with the health problem of constipation. Results: Before receiving acupressure therapy, the average patient had not defecated for 81 hours. Changes occurred after therapy, namely patients experienced defecation an average of 9.2 hours. Conclusions: The changes show that acupressure therapy is very significant in reducing constipation.